A Silicone Oil-Free Syringe Tailored for Intravitreal Injection of Biologics - Gjølberg, Torleif T.; Lode, Heidrun E.; Melo, Gustavo B.; Mester, Simone; Probst, Christine; Sivertsen, Magne S.; Jørstad, Øystein K.; Andersen, Jan Terje; Moe, Morten C. (Frontiers in Ophthalmology, 2022)
Intravitreal injections (IVI) of biologics targeting vascular endothelial growth factor (anti-VEGF) led to a paradigm shift in the management and prognosis of prevalent retinal conditions. Yet, IVI are typically performed with syringes that are neither developed nor approved for this purpose. Notably, syringes lubricated with silicone oil (SiO) are extensively used despite multiple reports showing that such syringes can cause deposition of SiO droplets in the vitreous body and patient discomfort. Thus, there is need for SiO-free substitutes specifically tailored for IVI. Here, we report on the development and testing of such a syringe. This syringe has no dead volume, and its design allows for high-accuracy dosing. Also, it permits pharmaceutical compounding and storage of bevacizumab, ranibizumab and aflibercept for up to 30 days without compromising their functional binding or transport properties. Finally, the new syringe demonstrated a favorable safety profile regarding release of SiO compared to SiO lubricated alternatives, including commercially prefilled syringes. Accordingly, the newly developed syringe is an appealing alternative for IVI.